An approach to pneumatosis intestinalis: Factors affecting your management. (2015) - Tahiri, Mehdi; Levy, Jordan; Alzaid, Saud; Anderson, Dawn
Highlights: Surgical intervention is necessary in patients that are unstable or in the presence of probable bowel wall compromise. Medical management of PI includes antibiotics, elemental diet and oxygen therapy. We propose a management algorithm for the treatment of PI based on clinical, laboratory and radiological findings. Abstract: Pneumatosis Intestinalis (PI) is defined as the presence of extra-luminal gas confined to the bowel wall. PI is an ominous condition often requiring emergent surgery. The management can be challenging in some circumstances, as the choice of surgery versus medical treatment can be difficult. In this study, we first report the case of a seventy-seven year old woman presenting to the emergency department with the presence of PI on computed tomography of the abdomen. Secondly, we review the existing literature regarding the management of PI and we suggest a treatment algorithm based on clinical, laboratory and radiological findings.